2005
DOI: 10.1002/jemt.20234
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of human intracisternal A‐type retroviral particles in autoimmunity

Abstract: Prior studies have linked retroviruses to various arthropathies and autoimmune diseases. Sjögren's syndrome (SS), a systemic autoimmune disease, is characterized by aggressive infiltration of lymphocytes into the salivary and lacrimal glands, resulting in destruction of the glands and dry mouth and eyes (sicca syndrome). The infiltrating lymphocytes in SS may become overtly malignant, and thus, the incidence of lymphoma is greatly increased in SS patients. A human intracisternal A-type retroviral particle type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 75 publications
(62 reference statements)
1
9
0
Order By: Relevance
“…Similar results were found by Yamano et al who also observed IAPs in epithelial cells of pSS patients with electron microscopy [20]. Later on, Sander et al showed that patients with pSS, systemic lupus erythematosus, Still's disease, and idiopathic T lymphocytopenia have antibodies against purified IAP proteins [21]. These results lead to several questions that deserve further investigation:…”
Section: Identification Of Retrovirus Particles In the Salivary Glandsupporting
confidence: 60%
“…Similar results were found by Yamano et al who also observed IAPs in epithelial cells of pSS patients with electron microscopy [20]. Later on, Sander et al showed that patients with pSS, systemic lupus erythematosus, Still's disease, and idiopathic T lymphocytopenia have antibodies against purified IAP proteins [21]. These results lead to several questions that deserve further investigation:…”
Section: Identification Of Retrovirus Particles In the Salivary Glandsupporting
confidence: 60%
“…[18][19][20] IAP may also be involved in the pathogenesis of certain autoimmune diseases. 21 An IAP element of 6026 base pairs is located in intron 23 of the ADAMTS13 gene in some strains of mice. 22 This IAP element is 92% homologous to the MIA14 IAP element (M17551) originally identified in the kappa light-chain gene of a mouse hybridoma cell line.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their abrupt appearance in a tissue, these proteins could bypass or override tolerance mechanisms that delete lymphocytes specific for constitutive self antigens. This antigen-based mechanism has been proposed in the context of multiple sclerosis [8], SLE [9], Sjogrens syndrome [10], and other autoimmune disorders in which specific retroviruses may give rise to the targeted autoantigens. Although the proteins of retroelements could in principle serve as antigens, there is no clear evidence for an autoimmune disease caused by autoreactive lymphocyte responses to endogenous retroviral antigens.…”
Section: Retroelements and Autoimmunitymentioning
confidence: 99%